Monetary Union Among Member Countries of the Gulf Cooperation Council - Fasano-Filho, Ugo.; Schaechter, Andrea (Washington, D.C. : International Monetary Fund, 2003)
The six member countries of the Gulf Cooperation Council (GCC)--Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates--have made important progress toward economic and financial integration, with the aim of establishing an economic and monetary union. This paper provides a detailed analysis of the economic performance and policies of the GCC countries during 1990-2002. Drawing on the lessons from the experience of selected currency and monetary unions in Africa, Europe, and the Caribbean, it assesses the potential costs and benefits of a common currency for GCC countries and also reviews the options for implementing a monetary union among these countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet